Gene-expression changes in knee-joint tissues with aging and menopause: implications for the joint as an organ - Rollick NC (Dove Medical Press, 2018)
Natalie C Rollick,1 Devin B Lemmex,1 Yohei Ono,1,2 Carol R Reno,1 David A Hart,1 Ian KY Lo,1 Gail M Thornton1,3 1McCaig Institute for Bone and Joint Health, Section of Orthopaedic Surgery, Department of Surgery, University of Calgary, Calgary, AB, Canada; 2Department of Orthopaedic Surgery, Nagoya University Graduate School of Medicine, Nagoya, Japan; 3Department of Orthopaedics, University of British Columbia, Vancouver, BC, Canada Background: When considering the “joint as an organ”, the tissues in a joint act as complementary components of an organ, and the “set point” is the cellular activity for homeostasis of the joint tissues. Even in the absence of injury, joint tissues have adaptive responses to processes, like aging and menopause, which result in changes to the set point.Purpose: The purpose of this study in a preclinical model was to investigate age-related and menopause-related changes in knee-joint tissues with the hypothesis that tissues will change in unique ways that reflect their differing contributions to maintaining joint function (as measured by joint laxity) and the differing processes of aging and menopause.Methods: Rabbit knee-joint tissues from three groups were evaluated: young adult (gene expression, n=8; joint laxity, n=7; water content, n=8), aging adult (gene expression, n=6; joint laxity, n=7; water content, n=5), and menopausal adult (gene expression, n=8; joint laxity, n=7; water content, n=8). Surgical menopause was induced with ovariohysterectomy surgery and gene expression was assessed using reverse-transcription quantitative polymerase chain reaction.Results: Aging resulted in changes to 37 of the 150 gene–tissue combinations evaluated, and menopause resulted in changes to 39 of the 150. Despite the similar number of changes, only eleven changes were the same in both aging and menopause. No differences in joint laxity were detected comparing young adult rabbits with aging adult rabbits or with menopausal adult rabbits.Conclusion: Aging and menopause affected the gene-expression patterns of the tissues of the knee joint differently, suggesting unique changes to the set point of the knee. Interestingly, aging and menopause did not affect knee-joint laxity, suggesting that joint function was maintained, despite changes in gene expression. Taken together, these findings support the theory of the joint as an organ where the tissues of the joint adapt to maintain joint function. Keywords: knee, aging, surgical menopause, joint as an organ